2020
DOI: 10.3389/fimmu.2020.01395
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Defense Mechanisms by Myeloid Cells That Hamper Cancer Immunotherapy

Abstract: Over the past decade, cancer immunotherapy has been steering immune responses toward cancer cell eradication. However, these immunotherapeutic approaches are hampered by the tumor-promoting nature of myeloid cells, including monocytes, macrophages, and neutrophils. Despite the arsenal of defense strategies against foreign invaders, myeloid cells succumb to the instructions of an established tumor. Interestingly, the most primordial defense responses employed by myeloid cells against pathogens, such as compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…Nowadays, it is well accepted that complement is a complex innate immune surveillance system, playing a key role in host homeostasis, inflammation, and defense [ 37 ]. In the tumor microenvironment, complement factors can perform nocanonical functions [ 23 ], such as stimulation of angiogenesis, inflammation, proliferation and migration, and they can even attenuate immunotherapy [ 25 , 67 ]. The therapeutic inhibition of complement components for cancer treatment has been well described [ 26 ], and the angogenesis-stimulating role of complements advocates the concept of applying mEHT in combination with angiogenesis inhibitors like Bevacizumab, which has been demonstrated to be beneficial for patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is well accepted that complement is a complex innate immune surveillance system, playing a key role in host homeostasis, inflammation, and defense [ 37 ]. In the tumor microenvironment, complement factors can perform nocanonical functions [ 23 ], such as stimulation of angiogenesis, inflammation, proliferation and migration, and they can even attenuate immunotherapy [ 25 , 67 ]. The therapeutic inhibition of complement components for cancer treatment has been well described [ 26 ], and the angogenesis-stimulating role of complements advocates the concept of applying mEHT in combination with angiogenesis inhibitors like Bevacizumab, which has been demonstrated to be beneficial for patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial amount of preclinical and clinical studies has indicated that tumor-associated myeloid cells, predominantly tumorassociated macrophages (TAMs), neutrophils, and myeloidderived suppressor cells (MDSCs), sustain an immunosuppressive tumor microenvironment, which is particularly refractory to both T cell trafficking and antitumor T cell functions (4,(129)(130)(131)(132)(133)(134). Extensive research in this field has additionally concluded that the specific targeting and/or elimination of this myeloid-driven immunosuppressive program can render the natural, induced, and engineered immunological responses against tumors more concrete and effective (135)(136)(137). In line with the above, here we first provide proof-of-principle evidence of this notion using the Mouse Mammary Tumor Virus Polyoma Middle-T antigen (MMTV-PyMT) mouse model of breast carcinoma, which successfully recapitulates human breast cancer progression (138).…”
Section: The Cancer Cell Dissemination Trajectory As An Immunosuppresmentioning
confidence: 99%
“…In recent years, the molecular/cellular investigation of the immune tumor microenvironment and the comprehensive studying of the immunosuppressive mechanisms harbored therein have been at the frontier of cancer research, as an attempt to improve the already promising landscape of cancer immunotherapy (1,86,132,135,151). In this regard, we offer a fresh perspective on the topic by distinguishing disparate sets of immunosuppressive mechanisms in different tumor microenvironments.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, tumor cells also develop mechanisms to evade immune surveillance and could mold myeloid cells to serve the tumor. Functionally, tumor-associated myeloid cells are often divided into anti- or pro-tumor subgroups [ 9 , 10 , 11 ]. The anti-tumoral group are associated with immunostimulatory cells with the secretion of pro-inflammatory cytokines (e.g TNF-α, IL-12, and IL-6).…”
Section: Introductionmentioning
confidence: 99%